Malignant Ewing-Like Neoplasm With an EWSR1-KLF15 Fusion: At the Crossroads of a Myoepithelial Carcinoma and a Ewing-Like Sarcoma. A Case Report With Treatment Options. (August 2018) - Stevens, Todd M.; Qarmali, Morad; Morlote, Diana; Mikhail, Fady M.; Swensen, Jeffrey; Gatalica, Zoran; Siegal, Gene P.; Conry, Robert M.
We present a case of a malignant Ewing-like neoplasm of the parotid gland in a 20-year-old woman with an EWSR1-KLF15 gene fusion that presented with pulmonary metastasis. Despite the fact that the tumor was essentially immunohistochemically negative for keratins, p63, and p40, we interpret this neoplasm as an unusual form of a high-grade myoepithelial carcinoma based on its focal plasmacytoid cytology, chondromyxoid matrix, SOX10, S100 protein, and calponin expression, and the knowledge that the EWSR1-KLF15 gene fusion has, to date, only been identified in 2 tumors, both myoepithelial carcinomas of the kidney. We also present a cytogenetic analysis of this unusual tumor. This "Ewing-like myoepithelial carcinoma" initially did not respond to 2 cycles of ifosfamide and etoposide alternated with a cycle of cytoxan, adriamycin, and vincristine, a standard regimen for Ewing sarcoma. Subsequent oral pazopanib therapy did result in a reduction of the patient's pulmonary and nodal disease.